Study and Synthesis of Benzimidazole Derivatives as Antibacterial Agents - Singh, C.P.; Kumar, S.; Nayal, S.S. (Asian Journal of Chemistry, 2010)
In the present note, the authors describe the preparation of benzimidazole derivatives and studied their antibacterial properties.